Afferent arteriolar vasodilator effect of adenosine predominantly involves adenosine A2B receptor activation - Feng, Ming-Guo; Navar, L Gabriel (American Journal of Physiology - Renal Physiology, 2010)
Adenosine is an important paracrine agent regulating renal vascular tone via adenosine A(1) and A(2) receptors. While A(2B) receptor message and protein have been localized to preglomerular vessels, functional evidence on the role of A(2B) receptors in mediating the vasodilator action of adenosine on afferent arterioles is not available. The present study determined the role of A(2B) receptors in mediating the afferent arteriolar dilation and compared the effects of A(2B) and A(2A) receptor blockade on afferent arterioles. We used the rat in vitro blood-perfused juxtamedullary nephron technique combined with videomicroscopy. Single afferent arterioles of Sprague-Dawley rats were visualized and superfused with solutions containing adenosine or adenosine A(2) receptor agonist (CV-1808) along with adenosine A(2B) and A(2A) receptor blockers. Adenosine (10 micromol/l) caused modest constriction and subsequent superfusion with SCH-58261 (SCH), an A(2A) receptor blocker, at concentrations up 10 micromol/l elicited only slight additional decreases in afferent arteriolar diameter with maximum effect at a concentration of 1 micromol/l (-11.0 +/- 2.5%, n = 6, P < 0.05). However, superfusion of adenosine-treated vessels with MRS-1754 (MRS), an A(2B) receptor blocker, elicited greater decreases in afferent arteriolar diameter (-26.0 +/- 4.7%, n = 5, P < 0.01). SCH did not significantly augment the adenosine-mediated afferent constriction elicited by MRS; however, adding MRS after SCH caused further significant vasoconstriction. Superfusion with CV-1808 dilated afferent arterioles (17.2 +/- 2.4%, n = 6, P < 0.01). This effect was markedly attenuated by MRS (-22.6 +/- 2.0%, n = 5, P < 0.01) but only slightly reduced by SCH (-9.0 +/- 1.1%, n = 5, P < 0.05) and completely prevented by adding MRS after SCH (-24.7 +/- 1.8%, n = 5, P < 0.01). These results indicate that, while both A(2A) and A(2B) receptors are functionally expressed in juxtamedullary afferent arterioles, the powerful vasodilating action of adenosine predominantly involves A(2B) receptor activation, which counteracts A(1) receptor-mediated vasoconstriction.